Institutional adjustment and change at the firm level: A varieties of capitalism perspective. Issue 2 (June 2015) - Kuznetsov, Andrei; Jacob, Marcus
Summary: This paper contributes to a better understanding of global corporate and industrial change at the firm level. Our focus is on convergence vs. divergence of national institutional systems. Data are drawn from a survey of German and UK firms. Our results for adaptation behavior of British subsidiaries in Germany suggest that at the firm level the primacy of national institutions and institutional complementarity as determinants of the organizational behavior of MNEs may be overstated. Nonetheless, evidence that German MNEs in Britain seek to choose strategic choices for which there is institutional support in the host country suggests that complementarity is functional enough to incite adjustment even in the absence of strong formal pressure. The evidence that both German and British firms seem to prefer practices characteristic of liberal market economies may pose a problem for institutional stability in Germany and generates implications for the likely pathways of institutional change.